Individualized visual narratives: type 1 diabetes management strategies among three runners in the London Marathon - Montt, Denise; Onetto, María Teresa; Sánchez, Raimundo (InfoDesign, 2023)
This study investigates the diabetes management strategies of three high-level athletes with Type 1 Diabetes (T1D) during the 43rd London Marathon. The athletes’ strategies, which included insulin dose adjustments, carbohydrate intake, and monitoring techniques, were analyzed using a collaborative autoethnographic approach and data from medical and running devices. The athletes, two males and one female, used various technologies such as Supersapiens, Freestyle Libre, and the Medtronic Minimed 780Ginsulin pump to manage their diabetes during the marathon. Despite individual challenges, all three athletes successfully completed the marathon. The study presents the strategies, glycemic data, and major highlights using visual narratives, providing valuable insights into the experiences of athletes with T1D during endurance events. These narratives effectively communicate the challenges faced by athletes with T1D and can help optimize diabetes management during endurance events.